PENYELENGGARAAN BADAN USAHA MILIK DESA BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA (STUDI KASUS DI DESA MUSIR KIDUL KECAMATAN REJOSO KABUPATEN NGANJUK) - Febrita Putri Wahanani; . Achmad (Res Publica: Jurnal Hukum Kebijakan Publik, 2024)
This writing aims to analyze the Implementation of Village-Owned Enterprises Law Number 6 of 2014 Concerning Villages (Case Study in Musir Kidul Village, Rejoso District, Nganjuk Regency) and the inhibiting factors. The research method used is an empirical legal method with descriptive research characteristics and a qualitative research approach. From the results of this study it can be concluded that the Implementation of Law Number 6 of 2014 concerning Village-Owned Enterprises in BUMDes in Musir Kidul Village, Rejoso District, Nganjuk Regency regarding establishment, organization, business formation, capital, management, and business development, in practice has been running, however there are several obstacles that make the implementation of Law Number 6 of 2014 concerning Villages Related to VillageOwned Enterprises less than optimal. Existing obstacles such as a lack of human resources in managing business units in BUMDesa Makmur Sentosa, unable to meet market demand, lack of public awareness, and the absence of articles governing grants and/or access to capital in Musir Kidul Village Regulation Number 6 of 2021 concerning Business Entities Village Owned.